Odpowiedź :
Odpowiedź:
a)
-3 - 4 * (-5)² = = 3 - 4 * 25 = 3 - 100 = -97
b)
(-2)² - 3 * (-4) - 7 = 4 + 12 - 7 = 16 - 7 = 9
c)
-6 - 2 * (-5)² - 6² = -6 - 2 * 25 - 36 = -6 - 50 - 36 = -42 - 50 = -92
d)
-7 - 3 * (-4)² - 10 = -17 - 3 * 16 = -17 - 48 = -65
e)
6 - (7 - 5²) - 3 * (-2) = 6 - (7 - 25) + 6 = 12 - (-18) = 12 + 18 = 30
f)
-3 * (-8) - 6 * 7² = 24 - 6 * 49 = 24 - 294 = -270
Szczegółowe wyjaśnienie:
Odpowiedź:
a) -3-4*(-5)^2= -3-4*25= -3-100 = -103
b) (-2)^2 - 3* (-4) - 7 = 4 + 12 - 7 = 9
c) -6 -2 * (-5)^2 - 6^2 = -6-2 * 25 - 36 = -6 - 50 - 36 = -92
d) -7-3*(-4)^2-10=-7-3*16-10 = -7-48 - 10 = -65
e) 6-(7-5^2)-3*(-2)=6 + 18 +6 = 30
f) -3 * (-8) - 6 * 7^2 = -3 * (-8) - 6 * 49 = 24 - 294 = -270
Wszystko jest dobrze na 100%
Szczegółowe wyjaśnienie: